A sensitive chemiluminescence enzyme immunoassay for the determination of deoxynivalenol in wheat samples. Issue 5 (5th February 2015) - Zhang, Rongsheng; Zhou, Yujun; Zhou, Mingguo
Abstract : A sensitive chemiluminescence enzyme immunoassay (CLEIA) was developed and applied for the determination of deoxynivalenol residue in wheat samples. Abstract : A competitive indirect chemiluminescence enzyme immunoassay (ci-CLEIA), capable of rapidly quantifying trace levels of deoxynivalenol (DON), was developed with a monoclonal antibody of DON. In addition, the monoclonal antibody was selected by comparing the half-maximal inhibition concentration (IC50 ), the limit of detection (LOD, IC10 ), and the affinity constant with another two antibodies. The effects of organic solvent (acetonitrile), Na + (NaCl) and pH were investigated. Under optimal conditions, the CLEIA allowed DON determination in a linear working range (IC20 –IC80 ) of 1.7–170 μg L −1 with an IC50 value of 17 μg L −1 and a LOD value of 0.49 μg L −1 . Recovery of 90.59–93.16% for the CLEIA was obtained from spiked samples. Furthermore, the results of CLEIA for the authentic samples correlated well with those of gas chromatography. The developed CLEIA would be ideally suitable for screening of DON contamination in wheat samples.